Population Genetic Structure and Gene Expression Plasticity of the Deep-Sea Vent and Seep Squat Lobster Shinkaia crosnieri - Xiao, Yao; Xu, Ting; Sun, Jin; Wang, Yan; Wong, Wai Chuen; Kwan, Yick Hang; Chen, Chong; Qiu, Jian-Wen; Qian, Pei-Yuan (Frontiers in Marine Science, 2020)
Shinkaia crosnieri (Munidopsidae) is a squat lobster that dominates both deep-sea hydrothermal vent and methane seep communities in the Western Pacific. Previous studies comparing S. crosnieri living in the two types of habitats have suffered from methodological and/or sample size limits. Here, using transcriptome-wide genetic markers from 44 individuals, we reveal the extent of genetic connectivity between a population of S. crosnieri collected from a methane seep in the South China Sea (SCS) and another collected from a hydrothermal vent in the Okinawa Trough (OT), as well as their signatures of local adaptation. Analysis of differentially expressed genes (DEGs) between these two populations and analysis of population-specific genes (PSGs) revealed that a great number of unigenes, such as cytochrome P450 (CYP), glutathione S-transferase (GST) and peroxiredoxin 6 (Prdx6) related to oxidoreductase, and sulfur dioxygenase (ETHE1) and chondroitin 4-sulfotransferase 11 (CHST11) related to sulfur metabolism, showed opposite expression patterns in these two populations. Data subsampling revealed that at least five individuals per site are required to generate reliable results from differential gene expression analysis. Population genetic analyses based on 32,452 single-nucleotide polymorphisms (SNPs) revealed clear genetic differentiation between these two populations with an FST value of 0.07. Analysis of outlier SNPs revealed 345 unigenes potentially under positive selection, such as sarcosine oxidase/L-pipecolate oxidase (PIPOX), alanine-glyoxylate transaminase/serine-glyoxylate transaminase/serine-pyruvate transaminase (AGXT), and Cu-Zn superoxide dismutase (SOD1). Different gene expressions and amino acid substitutions of some genes between the two sites related to oxidation resistance and xenobiotic detoxification may indicate adaptation to the specific environmental conditions of each site. Overall, exploring the population structure of S. crosnieri using transcriptome-wide SNP markers resulted in an improved understanding of its molecular adaptation and expression plasticity in vent and seep ecosystems.